Recovery of PGM's from a copper oxidising leach residue : Rustenburg Base Metal Refinery Anglo Platinum - De Beer, Ronald (Centre for Bioprocess Engineering Research, 2014)
Includes abstract. Includes bibliographical references (leaves 164-167).